(untitled) (Open Academia: Journal of Scholarly Research, 2026)
This article examines the problem of intersubjectivity in the philosophical views of Ludwig Wittgenstein, focusing on the transformation of his ideas from early logical atomism to later linguistic philosophy. The study analyzes how intersubjectivity is implicitly articulated through Wittgenstein’s concepts of language-games, forms of life, and rule-following practices. Special attention is given to the rejection of private language and its implications for understanding shared meaning and mutual comprehension among individuals. The research employs a hermeneutic and comparative methodological approach, examining primary texts such as Philosophical Investigations alongside relevant secondary literature. It argues that Wittgenstein’s later philosophy provides a non-metaphysical foundation for intersubjectivity, grounding it in socially embedded linguistic practices rather than in transcendental or purely subjective structures